Global smoking-related deaths averted due to MPOWER policies implemented at the highest level between 2007 and 2020 - Greg Lyle; Delia Hendrie (BMC, 2024)
Abstract Background In response to the harm caused by tobacco use worldwide, the World Health Organization (WHO) World Health Assembly actioned the WHO Framework Convention on Tobacco Control (FCTC) in 2005. To help countries meet their FCTC obligations, the WHO introduced in 2008 the MPOWER policy package and by 2020 the FCTC had been ratified by 182 parties. The package consists of six evidence-based demand reduction smoking cessation policies to assist countries to achieve best practice. We used published evaluation results and replicated the published model to estimate current policy achievement and demonstrate the impact and equity of the MPOWER policy package in reducing the global number of smokers and smoking-attributable deaths (SADs) between 2007 and 2020. Methods We replicated an evaluation model (the Abridged SimSmoke model) used previously for country impact assessments and validated our replicated reduction in SADs for policies between 2014 and 2016 against the published results. The replicated model was then applied to report on the country level SADs averted from achieving the highest level of implementation, that is best practice in MPOWER policies, between 2016 and 2020. The latest results were then combined with past published results to estimate the reduction in SADs since the commencement of the MPOWER policy package. Country level income status was used to investigate the equity in the uptake of MPOWER policies worldwide. Results Identical estimates for SADs in 41 out of 56 MPOWER policies implemented in 43 countries suggested good agreement in the model replication. The replicated model overestimated the reduction in SADs by 159,800 (1.5%) out of a total of 10.5 million SADs with three countries contributing to the majority of this replication discrepancy. Updated analysis estimated a reduction of 8.57 million smokers and 3.37 million SADs between 2016 and 2020. Between 2007 and 2020, 136 countries had adopted and maintained at least one MPOWER policy at the highest level which was associated with a reduction in 81.0 million smokers and 28.3 million SADs. Seventy five percent of this reduction was in middle income countries, 20% in high income and less than 5% in low income countries. Conclusions Considerable progress has been made by MPOWER policies to reduce the prevalence of smokers globally. However, there is inequality in the implementation and maintenance, reach and influence, and the number of SADs averted. Future research to modify the model could provide a more comprehensive evaluation of past and future progress in tobacco control policies, worldwide.